Factual belief polarization between Democrats and Republicans: source or epiphenomenon of ideological and affective polarization? - Rekker, Roderik (Frontiers in Political Science, 2024)
Democrats and Republicans have polarized in their attitudes (i.e., ideological polarization) and their feelings toward each other (i.e., affective polarization). Simultaneously, both groups also seem to diverge in their factual beliefs about reality. This preregistered survey experiment among 2,253 American citizens examined how this factual belief polarization may or may not fuel ideological and affective polarization around four key issues: income differences, immigration, climate change, and defense spending. On all issues except immigration, Democrats and Republicans were equally or more divided in their factual beliefs about the present than in their ideals for the future. Corrective information decreased partisan polarization over some ideals, but not directional policy attitudes. Priming respondents' factual beliefs conversely increased polarization around defense spending, but not other issues. Much remains unclear about the complex relation between factual beliefs and polarization, but measuring ideals and priming beliefs could be promising avenues for future research.